Rainfall Duration’s Impact on Mining Earthmoving Equipment Performance – Case Study at PT. BUMA GEO-AJE, South Kalimantan - Nandang Lukmanul Basar; Hartono; Siti Muawanah Robial (Jurnal Teknik Sipil dan Perencanaan, 2024)
This study investigates the impact of rainfall duration on the performance of earthmoving equipment at PT BUMA, GEO-AJE, South Kalimantan. Data from April 2023 covering 29 days were analyzed using SPSS 22 and Origin 2024. The study revealed a 7.06637% decrease in excavator and dump truck efficiency per hour of rainfall. Cycle times were increased by 0.15122 minutes for excavators and 4.50034 minutes for dump trucks per hour of rain. Moreover, excavator productivity declined by 1138.82900 bcm/day and dump truck productivity by 176.21836 bcm/day. These results highlight the necessity of accounting for rainfall in mining operations, especially in productivity forecasts and equipment management.